1996
DOI: 10.1016/s0304-3959(96)03221-6
|View full text |Cite
|
Sign up to set email alerts
|

The initial effects of a cervical spine manipulative physiotherapy treatment on the pain and dysfunction of lateral epicondylalgia

Abstract: Manipulative therapy is frequently used in the management of musculoskeletal pain. A frequently reported clinical feature of this treatment is the immediacy with which it appears to initiate improvement in pain and function. A randomised, double blind, placebo controlled, repeated measures design was employed to study the initial effects of a cervical spine treatment technique in a group of 15 patients with lateral epicondylalgia. Pressure pain threshold, pain-free grip strength, upper limb neurodynamics, pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
253
3
20

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(286 citation statements)
references
References 21 publications
10
253
3
20
Order By: Relevance
“…9,11,15,[19][20][21][22][23] An example of such an intervention includes the cervical lateral glide mobilization with the involved upper extremity placed in a position designed to take up the slack in the brachial plexus. 16,21,24,25 However, several authors have advised against applying cervical spine mobilization techniques to patients who demonstrate either normal or excessive mobility of the cervical spine, 26,27 which may include some patients with cervicobrachial syndrome. 17 Hypermobility is a frequent finding in patients with whiplash-associated disorder, 28 a group who commonly reports neck and arm pain.…”
Section: Introductionmentioning
confidence: 99%
“…9,11,15,[19][20][21][22][23] An example of such an intervention includes the cervical lateral glide mobilization with the involved upper extremity placed in a position designed to take up the slack in the brachial plexus. 16,21,24,25 However, several authors have advised against applying cervical spine mobilization techniques to patients who demonstrate either normal or excessive mobility of the cervical spine, 26,27 which may include some patients with cervicobrachial syndrome. 17 Hypermobility is a frequent finding in patients with whiplash-associated disorder, 28 a group who commonly reports neck and arm pain.…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to speculate the mechanism of action by which the counterforce forearm brace achieved its effects in improving grip strength. One possible explanation is that a direct mechanical effect on the muscles of the forearm somehow improved the internal (SnyderMackler & Epler, 1989;Vicenzino, Collins, & Wright, 1996). The theory of the mechanical effect on muscle is similar to that postulated, but not proven, for other orthotic braces for this condition (Snyder-Mackler & Epler;Vicenzino, Brooksband, Minto, Offord, & Paungmali, 2003).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, although this study did not identify the range of joint motions, we think that the recovery of mobility achieved by thoracic mobilizations affected all the measured parameters. Earlier studies [17][18][19] indicated that manual therapy interventions to the spine were effective in alleviating pain occurring in areas distal to the area being directly treated. It has also been reported that the reason why manual therapy conducted on the spine shows alleviation of pain is that it stimulates inhibition mechanisms 20) .…”
Section: Discussionmentioning
confidence: 99%